CRE Learning in the Digital Age: An Inclusive Approach to Achieving Religious Moderation Amidst Diversity - Zega, Yanuar Ada; Tapilaha, Sandra Rosiana; Sisi, Sisi (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This article explores the implementation of Christian Religious Education (CRE) in the digital era, with a focus on inclusivism to promote religious moderation in the face of diversity. The background of this research is the increasing challenge of teaching CRE in religiously diverse environments. This study employs literature analysis to examine theories of religious education and religious moderation, as well as evaluate digital platforms used in CRE. This research aims to identify effective teaching strategies that promote inclusive and tolerant attitudes. The novelty of this research lies in its interdisciplinary approach, combining studies in education, technology, and theology. The findings indicate that the use of digital technology can enhance students' understanding of inclusivism and religious moderation values. In conclusion, the integration of technology in CRE has significant potential to strengthen inclusive attitudes in a pluralistic society.